Hydrogen Sulfide Inhibits Inflammatory Pain and Enhances the Analgesic Properties of Delta Opioid Receptors - Aina Porta; Laura Rodríguez; Xue Bai; Gerard Batallé; Gerard Roch; Enric Pouso-Vázquez; Gianfranco Balboni; Olga Pol (MDPI AG, 2021)
Chronic inflammatory pain is present in many pathologies and diminishes the patient's quality of life. Moreover, most current treatments have a low efficacy and significant side effects. Recent studies demonstrate the analgesic properties of slow-releasing hydrogen sulfide (H2S) donors in animals with osteoarthritis or neuropathic pain, but their effects in inflammatory pain and related pathways are not completely understood. Several treatments potentiate the analgesic actions of δ-opioid receptor (DOR) agonists, but the role of H2S in modulating their effects and expression during inflammatory pain remains untested. In C57BL/6J male mice with inflammatory pain provoked by subplantar injection of complete Freund's adjuvant, we evaluated: (1) the antiallodynic and antihyperalgesic effects of different doses of two slow-releasing H2S donors, i.e., diallyl disulfide (DADS) and phenyl isothiocyanate (P-ITC) and their mechanism of action; (2) the pain-relieving effects of DOR agonists co-administered with H2S donors; (3) the effects of DADS and P-ITC on the oxidative stress and molecular changes caused by peripheral inflammation. Results demonstrate that both H2S donors inhibited allodynia and hyperalgesia in a dose-dependent manner, potentiated the analgesic effects and expression of DOR, activated the antioxidant system, and reduced the nociceptive and apoptotic pathways. The data further demonstrate the possible participation of potassium channels and the Nrf2 transcription factor signaling pathway in the pain-relieving activities of DADS and P-ITC. This study suggests that the systemic administration of DADS and P-ITC and local application of DOR agonists in combination with slow-releasing H2S donors are two new strategies for the treatment of inflammatory pain.